2016
DOI: 10.1139/cjpp-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect oftrans-Chalcone on experimentally induced hepatic injury in rats: inhibition of hepatic inflammation and fibrosis

Abstract: The current study investigated the hepatoprotective effect of trans-Chalcone in carbon tetrachloride (CCl4) and paracetamol (PCM) induced liver damage in rats. Administration of CCl4 and PCM (1 mL/kg, i.p., 3 days, and 2 g/kg, p.o., single dose, respectively) produced hepatic injury. Ponderal changes (percent change in body mass and relative liver mass) and biochemical parameters (serum ALT, AST, ALP, bilirubin) were estimated. The markers of oxidative and nitrosative stress (TBARS, reduced GSH, nitrite and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Additionally, the profibrogenic cytokine TGF‐β1 can up‐regulate the deposition of extracellular matrix (ECM) . Studies on some chalcones recently reported on their hepatoprotectivity against chemical intoxication via inhibition of hepatic fibrosis markers . In this research, the fibrogenesis markers, PDGF and TGF‐β1 were down‐regulated in the animals treated with the isolated chalcone PA in the same manner as the Silymarin‐treated animals in contrast to those of cirrhotic controls (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, the profibrogenic cytokine TGF‐β1 can up‐regulate the deposition of extracellular matrix (ECM) . Studies on some chalcones recently reported on their hepatoprotectivity against chemical intoxication via inhibition of hepatic fibrosis markers . In this research, the fibrogenesis markers, PDGF and TGF‐β1 were down‐regulated in the animals treated with the isolated chalcone PA in the same manner as the Silymarin‐treated animals in contrast to those of cirrhotic controls (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Trans-chalcone (1,3-diphenyl-2-propen-1-one) is a flavonoid precursor that can be obtained from plants such as Piper methysticum (Kava-Kava), Aniba riparia and Didymocarpus corchorijolia [145]. Trans-chalcone presents in vivo antioxidant effects [42,145] and anti-hyperalgesic mechanisms through the inhibition of leukocyte recruitment, IL-1β, TNF-α, and IL-6 production, and NLRP3 inflammasome activation in macrophages stimulated with MSU crystals [42]. It also inhibits VEGF and ICAM-1 expression and activation of STAT3 and NF-κB [41], indicating that part of its analgesic mechanism is related to the blockade of NF-κB-dependent pro-inflammatory mediators.…”
Section: Chalconementioning
confidence: 99%
“…Moreover, as shown by Singh et al (2016a), this chalcone reduced markers of liver injury (AST and ALT) and infl ammation (TNF-α) in toxicant induced liver injury. Hence, anti-infl ammatory eff ect of trans-chalcone may be involved in its hepatoprotective eff ect (Singh et al 2016a).…”
Section: Discussionmentioning
confidence: 71%
“…Hepatoprotective eff ect of trans-chalcone and its ability to reduce serum levels of AST and ALT has been shown by Karkhaneh et al (2016). Moreover, as shown by Singh et al (2016a), this chalcone reduced markers of liver injury (AST and ALT) and infl ammation (TNF-α) in toxicant induced liver injury. Hence, anti-infl ammatory eff ect of trans-chalcone may be involved in its hepatoprotective eff ect (Singh et al 2016a).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation